К изучению морфологической изменчивости щуки обыкновенной из некоторых рек Украины - Щербуха, А.Я. (Вестник зоологии, 1974)
The meristic characters of Esox lucius L. from the populations of the Dniester, South Bug, Dnieper and Seversky Donets are established to vary almost within the same limits. The mentioned populations were compared by 25 plastic characters. The trustworthy differences between the populations were found in three — eight characters. The degree of difference between the Esox lucius L. populations from the rivers under study is shown by the E. S. Smirnov (1969) method of taxonomic analysis.